Analysis of the Revocation of the Jakarta Student Excellence (KJMU) Card Program for Underprivileged Students - Fitria Auldri Desiana; Muhammad Aras Prabowo; Muhammad Ashlyzan Razik (Trescode Green Organization, 2024)
Because of the large number of students or students who want to study in universities, there was the emergence of KJMU social assistance funds or the Jakarta Mahasiwa Unggul card. However, in its implementation, the funds are not right on target or accepted by students who are able to finance their academic needs. This can be seen through the receipt of KJMU who received pocket money from his parents. With the occurrence of the wrong target of the KJMU recipient. There has been an issue of revocation of KJMU receipt funds by the governor of DKI Jakarta, Mr. Heru. This analysis aims to solve the issue of the problem of revocation of the KJMU. The methodology used in this research is the study of literature that includes systematic analysis of various sources such as journals, books, and reports. The results of the analysis found that there was no revocation of KJMU for students who had received funds given by KJMU. However, the governor of DKI Jakarta only records the data of the poor who are suitable in the receipt of KJMU. Students who have received KJMU funds will continue to be financed until they graduate.